(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Education industry is a big contributor in Indian service sector in terms of providing employment and eventually contributes to the factor determining national GDP. In the continuation, issues and challenges related to Work life balance have been gaining attention as well. These issues have been observed to be more prominent in service sector. However, various researchers and studies have developed few scales to measure work life balance but current study is an attempt to define a much elaborative and precise scale for the measurement of WLB in education industry. In present work, a 30 items scale defined under three factors is designed to measure WLB of academicians working in education industry. The data for the purpose was collected from a sample of 125 academicians working in private universities in Jaipur City. The reliability and validity of the scale has been tested by using Cronbach Alpha analysis.